(untitled) (International Journal of Applied Research in Management and Economics, 2025)
This paper intends to determine the impact of the COVID-19 pandemic on Small, Medium and Micro Enterprises, generally referred to as SMEs. The case study is on the Pay TV installation sector in Johannesburg, a city in South Africa. The article further ascertains if Pay TV installers were able to cope with the pandemic due to limited operational and financial resources as a result of the pandemic. The use of qualitative research is deemed suitable for this study to determine the opinions, thoughts, and feelings of SMEs in the Pay TV installation sector in Johannesburg whose operations were affected by the COVID-19 pandemic. The population of Pay TV installers is estimated to be 117. Since this number is quite large and would serve impractical to base the research on the entire population, an approach of sampling Pay TV installation SMEs in the Johannesburg area was adopted. The authors sampled 11 Pay TV installers as participants, which they considered enough to achieve data saturation and article objectives. Amongst others, the article findings indicate that the constrained movement of people limited word-of-mouth advertising. Some participants got infected with COVID-19 and other participants had employees that were infected. Furthermore, poor administration of government financial assistance applications caused additional strain on Pay TV installation businesses. The overall impact of this was limited business continuity.